Edukasi Tablet Tambah Darah pada Remaja Putri SMPN Satap 1 Watubangga, Desa Sumber Rejeki, Kecamatan Watubangga, Kabupaten Kolaka - Ilyas, Ika Lismayani; Sari, Erin Adelia; Arifin, M. Jaenal; Kholifah, Ira Nur; Maharani, Maharani; Fizria, Heny; Nurfa, Nurfa; Yunita, Sang Ayu; Khaer, Miftahul; Anang, Muh.; Saputri, Ritmayana; Kalsum, Ummi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Sumber Rejeki Village, Watubangga District, has a coastal character that contributes to family lifestyles. The goal of this community service (PKM) is to improve anemia literacy and Menstrual Health Management (MHM) among female students of SMPN Satap 1 Watubangga through educational outreach. This Community Service used a one-group pre-post design with a slide- and leaflet-based outreach approach without pharmacological intervention. The population was female adolescents in grades VII–IX; a total sampling of participants was conducted (N=18; July 2025; session duration 75–90 minutes). The variables assessed were Knowledge (K), Attitude (A), and Intention to Practice. The instrument consisted of a brief KAP questionnaire (5 items on the true/false K scale, 5 items on the Likert scale 1–5, and 3 items on the intention to practice). The average score increased from 63.9% (pre-session) to 91.1% (post-session) (Δ=+27.2 percentage points; t(17)=5.34; d=1.26—large effect size). The category composition shifted from Good=6, Fair=7, Poor=5 to Good=16, Fair=2, Poor=0 at post-session. The single-session, slide- and leaflet-based outreach program had a significant impact on improving anemia and MHM literacy among adolescent girls.